The influence of e-service quality, e-trust, on e-loyalty QRIS BCA with mediation by e-satisfaction (study on QRIS BCA users in Jakarta) - Bella Lorenza; Saparso Saparso (Journal of Multidisciplinary Academic and Practice Studies, 2025)
This study investigates the influence of E-Service Quality and E-Trust on E-Loyalty, with E-Satisfaction as a mediating variable, in the context of BCA QRIS users in Jakarta. The research is motivated by the growing trend of digital payments, especially QRIS-based transactions, which have shown significant growth in volume according to ASPI Indonesia. Methodology/approach: A quantitative approach was employed using primary data collected via an online questionnaire distributed through Google Forms. The study involved 113 active BCA QRIS users selected through purposive sampling. Data were analyzed using the Structural Equation Modeling (SEM) method with SmartPLS 4.0 software. The measurement scale used was a 5-point Likert scale. Results/findings: The results revealed that: (1) E-Service Quality has a positive but not significant effect on E-Loyalty; (2) E-Trust does not significantly influence E-Loyalty; (3) E-Service Quality has a positive but not significant impact on E-Satisfaction; (4) E-Trust positively and significantly influences E-Satisfaction; (5) E-Satisfaction significantly affects E-Loyalty; (6) E-Service Quality does not affect E-Loyalty through E-Satisfaction; (7) E-Trust positively affects E-Loyalty through E-Satisfaction. Conclusions: E-Satisfaction plays a crucial mediating role between E-Trust and E-Loyalty. However, E-Service Quality does not significantly influence E-Loyalty, either directly or indirectly. Limitations: The study is limited to a specific geographical area (Jakarta) and a relatively small sample size. Data collection was conducted online, which may introduce response bias. Contribution: This research contributes to the literature on digital payment behavior and provides managerial implications for enhancing user trust and satisfaction to foster loyalty.